Palivizumab reimbursement criteria and neonatal RSV hospitalisation: a regional retrospective review - Marina Davoli; Federico Marchetti; Antonio Addis; Valeria Belleudi; Marco Finocchietti (BMJ Publishing Group, 2021)
In Italy, reimbursement restrictions regarding palivizumab prophylaxis approved in 2016 have been revoked in 2017, restoring use in infants with Gestational Age (GA) >29 weeks. Respiratory Syncytial Virus (RSV) hospitalisations and prevalence of palivizumab use in infants aged <6 months during five seasons (2014-2019), were considered according to different GA. Although RSV hospitalisations rate showed no significant changes, during different seasons in all GA, lower prevalence of palivizumab use in 2016 (0.8% vs 0.3%), returned to a higher level following the revoke of restrictions. Changes in reimbursement criteria were not associated with neonatal RSV hospitalisations rate but with a significant impact on palivizumab use.